Interactively browsing movies in terms of action, foreshadowing and resolution - Greenhill, Stewart; Adams, Brett; Venkatesh, Svetha (ACM, 2010)
We describe a novel video player that uses Temporal Semantic Compression (TSC) to present a compressed summary of a movie. Compression is based on tempo which is derived from film rhythms. The technique identifies periods of action, drama, foreshadowing and resolution, which can be mixed in different amounts to vary the kind of summary presented. The compression algorithm is embedded in a video player, so that the summary can be interactively recomputed during playback.